The role of digital promotion in enhancing hotel competitiveness in Bali’s tourism sector - Kencanawati, Anak Agung Ayu Mirah; Meirejeki, I Nyoman; Supiatni , Ni Nyoman; Suarta, I Ketut (YAYASAN MITRA PERSADA NUSANTARA, 2025)
- In the digital era, hotel businesses are increasingly adopting digital promotional strategies due to their cost-effectiveness, speed, and ability to reach wide and diverse audiences. This study explores the role of digital promotion in enhancing hotel competitiveness in Bali’s tourism sector. Specifically, it aims to (1) identify which digital marketing media are predominantly utilized by hotel marketing departments, and (2) assess the impact of these digital tools on hotel room sales. To achieve these objectives, the research employs a qualitative descriptive method supported by data collection techniques such as observation, documentation, and interviews with marketing personnel across selected hotels in Bali. The analytical framework is based on digital promotion indicators, namely social media marketing, online advertising, official websites, and digital-based personal selling. The findings reveal that social media platforms—particularly Instagram—are the most dominant digital promotion tools used by hotels. Their visual-centric nature and real-time interaction features are highly effective in engaging potential tourists, especially among younger demographics. Additionally, websites integrated with booking engines and online advertising strategies also contribute significantly to driving direct bookings and enhancing consumer trust. The analysis further indicates a positive correlation between active digital promotion efforts and increased room occupancy rates. Hotels that consistently invest in curated digital content, interactive campaigns, and influencer collaborations have experienced notable growth in customer reach and booking conversions. In conclusion, digital promotion has become an essential marketing strategy for hotels in Bali. Its strategic use not only enhances visibility and brand awareness but also drives measurable improvements in room sales. Continued adaptation to emerging digital trends is recommended to maintain competitiveness in the evolving tourism landscape.